Menggali Sejarah Dan Makna Filosofis Rumah Adat Tongkonan Ke’te Kesu Di Toraja Utara - Rio, Azzhary Muh.; Syaidina. R, Alifia; Asdar, Mudzaffar Qatas; Nurfatimah, Nurfatimah; Mangalla, Yerestina Rembong; Pratiwi, Elfira; Irdahardini, Irdahardini; Baci, Muhammad Ihsan; Sunandar, Ikbal; Wantisa, Yunita Ella; Taba, Ismiyati (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
The Tongkonan traditional house is a symbol of the culture and identity of the Toraja people, especially in Ke'te Kesu. Tongkonan architecture represents social and spiritual values and is influenced by natural physical conditions. This research aims to analyze how geographical aspects, such as undulating topography, geological conditions, and tropical climate, influence the design, layout, and materials of Tongkonan buildings. In addition, this research explores the philosophical meaning of Tongkonan architecture as a form of response to the physical environment. The method is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation studies. Secondary data were obtained from literature, research reports, and official sources. The results show that geographical conditions play a significant role in determining the orientation and structure of Tongkonan. The harmony between architecture and environment creates a functional and aesthetic building and reflects the Toraja people’s local wisdom. In addition, Tongkonan serves as a social, cultural, and spiritual center, preserving ancestral heritage and strengthening community ties. This study confirms that Tongkonan preservation is important for maintaining cultural identity and contributing to environmental sustainability and the welfare of the Ke'te Kesu community. Therefore, the conservation policy of traditional architecture should consider the geographical aspects and cultural values attached to Tongkonan.